Systematic debriefing after qualitative encounters: an essential analysis step in applied qualitative research - McMahon-Rössle, Shannon A.; Winch, Peter J. (BMJ global health, 2018)
Conversations regarding qualitative research and qualitative data analysis in global public health programming often emphasize the product of data collection (audio recordings, transcripts, codebooks and codes), while paying relatively less attention to the process of data collection. In qualitative research, however, the data collector’s skills determine the quality of the data, so understanding data collectors’ strengths and weaknesses as data are being collected allows researchers to enhance both the ability of data collectors and the utility of the data. This paper defines and discusses a process for systematic debriefings. Debriefings entail thorough, goal-oriented discussion of data immediately after it is collected. Debriefings take different forms and fulfill slightly different purposes as data collection progresses. Drawing from examples in our health systems research in Tanzania and Sierra Leone, we elucidate how debriefings have allowed us to: enhance the skills of data collectors; gain immediate insights into the content of data; correct course amid unforeseen changes and challenges in the local context; strengthen the quality and trustworthiness of data in real time; and quickly share emerging data with stakeholders in programmatic, policy and academic spheres. We hope this article provides guidance and stimulates discussion on approaches to qualitative data collection and mechanisms to further outline and refine debriefings in qualitative research.